Design and development of a wideband vivaldi antenna array - Jiang, Zhao (2013)
This report presents a final year project study of wideband Vivaldi antennas for radar antenna array applications. After a literature review and introduction of antenna fundamentals, the study focuses on three types of ultra-wide band antennas, namely, tapered-slot antenna, antipodal vivaldi antenna, and a proposed simple step-slot antenna. This study includes theoretical analysis, computer-aided design by the commercial software FEKO, fabrication, and measurement testing. Much of the emphasis is on learning and understanding the popular tapered-slot antenna and antipodal Vivaldi antenna. But these two types of antennas are sensitive to their geometries and fabrication tolerance. Therefore, a simplified variation of tapered-slot antenna, namely, step-slot antenna is proposed with intention of similar performance and simpler structure for easier fabrication and lower product cost. The antennas studied in this project may find many defense and commercial applications.